Puerariae Radix protects against ulcerative colitis in mice by inhibiting NLRP3 inflammasome activation - Yu Ga; Yuanyuan Wei; Qingyu Zhao; Yimeng Fan; Yannan Zhang; Zhifang Zhang; Sijia Hao; Lixia Wang; Zhifen Wang; Jinlong Han; Shuang Wu; Zhihui Hao (Food Science and Human Wellness)
Ulcerative colitis (UC) is a common infl ammatory disease of the gastrointestinal tract. Traditional Chinese medicine (TCM) has long been used in Asia as a treatment for UC and Puerariae Radix (PR) is a reliable anti-diarrheal therapy. The aims of this study were to investigate the protective effect of PR using the dextran sulfate sodium salt (DSS)-induced UC model in mice and identify molecular mechanisms of PR action. The chemical constituents of PR via ultra-performance liquid chromatography/tandem mass spectrometry and identifi ed potential PR and UC targets using a network pharmacology (NP) approach were obtained to guide mouse experiments. A total of 180 peaks were identifi ed from PR including 48 flavonoids, 46 organic acids, 14 amino acids, 8 phenols, 8 carbohydrates, 7 alkaloids, 6 coumarins and 43 other constituents. NP results showed that caspase-1 was the most dysregulated of the core genes associated with UC. A PR dose of 0.136 mg/g administered to DSS treated mice reversed weight loss and decreased colon lengths found in UC mice. PR also alleviated intestinal mucosal shedding, infl ammatory cell infi ltration and mucin loss. PR treatment suppressed upregulation of NOD-like receptor protein 3 (NLRP3), cysteinyl aspartate-specific proteases-1 (caspase-1), apoptosis-associated speck-like (ASC) and gasdermin D (GSDMD) at both the protein and mRNA expression levels. The addition of a small molecule dual-specifi city phosphatase inhibitor NSC 95397 inhibited the positive effects of PR. These results indicated that PR exerts a protective effect on DSS-induced colitis by inhibiting NLRP3 infl ammasome activation in mice.